2018
DOI: 10.1016/j.trc.2018.02.022
|View full text |Cite
|
Sign up to set email alerts
|

Aircraft initial mass estimation using Bayesian inference method

Abstract: Aircraft mass is a crucial piece of information for studies on aircraft performance, trajectory prediction, and many other topics of aircraft traffic management. However, It is a common challenge for researchers, as well as air traffic control, to access this proprietary information. Previously, several studies have proposed methods to estimate aircraft weight based on specific parts of the flight. Due to inaccurate input data or biased assumptions, this often leads to less confident or inaccurate estimations.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
24
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 44 publications
(30 citation statements)
references
References 10 publications
0
24
0
Order By: Relevance
“…This study is an extension of our previous preliminary research of Sun et al (2018a), with an improved system model and new insights. Unlike Alligier et al (2015) where the machine learning models use mass estimations from regression methods as training input, or Chati and Balakrishnan (2018) where the machine learning model uses flight recorder data as training input, our method is a purely model-based state estimation approach.…”
Section: Introductionmentioning
confidence: 81%
See 1 more Smart Citation
“…This study is an extension of our previous preliminary research of Sun et al (2018a), with an improved system model and new insights. Unlike Alligier et al (2015) where the machine learning models use mass estimations from regression methods as training input, or Chati and Balakrishnan (2018) where the machine learning model uses flight recorder data as training input, our method is a purely model-based state estimation approach.…”
Section: Introductionmentioning
confidence: 81%
“…However, regression analysis requires the exploitation of model linearity. Recently Sun et al (2018b) has shown that ADS-B data availability makes it worthwhile to use Bayesian inference methods for the estimation of aircraft mass. The goal of this article is to extend this Bayesian inference approach such that it can incorporate non-linear aircraft evolution equations for the nonlinear Bayesian filtering of aircraft mass, based on ADS-B and Enhanced Mode-S surveillance data.…”
Section: Introductionmentioning
confidence: 99%
“…We consider the mass as a uniformly distributed random variable at each time step. Unlike the informed mass assumption addressed in Sun et al (2018a), the uniformed distribution considers all masses as equally possible. It is sampled together with all other parameters.…”
Section: Uncertaintiesmentioning
confidence: 99%
“…Delahaye et al proposed estimations of the True Air Speed and the wind using radar data [11], [12]. Sun et al estimate the aircraft mass using Bayesian inference methods [13]. Chati et al proposed different learning model types such as Gaussian Process regression [14] and tree-based classification [15] to predict the aircraft fuel flow rate.…”
Section: State Of the Artmentioning
confidence: 99%